Pertanggungjawaban Hukum Perusahaan Batubara Terhadap Pemenuhan Prestasi Akibat Larangan Ekspor Ditinjau Dari Hukum Positif Indonesia - Adinda Vinka Maharani; Suraji Suraji (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2024)
This research aims to determine the legal responsibilities of coal companies in fulfilling their achievements due to the export ban. This legal writing is included in the type of normative legal research using a legislative approach including primary legal materials and secondary legal materials collected through document study and analyzed using deductive legal material analysis using the syllogism method. This research examines the implementation of the Decree of the Minister of Energy and Mineral Resources Number 139.K/HK.02/MEM.B/2021 regarding the fulfillment and prioritization of domestic coal needs. The failure to fulfill the Domestic Market Obligation then gave rise to an export ban by the Ministry of Energy and Mineral Resources through the issuance of Circular Letter from the Directorate General of Minerals and Coal, Ministry of Energy and Mineral Resources Number B-605/MB.05/DJB.B/2021. The export ban then causes coal entrepreneurs to be unable to fulfill agreements with foreign companies. Non-fulfillment of achievements due to changes in Government policy in the form of an export ban is analyzed and categorized as force majeure so that non-performance, compensation or cancellation of the agreement cannot be sued. The legal responsibility that can be carried out by coal entrepreneurs in the event of an export ban is to submit a force majeure situation and prove that their party has been in good faith from the beginning until the agreement is in progress.